3D Finite‐Element Simulation of Wedge Splitting Test of Non‐Standard Ceramic Double Cantilever Beam with Chevron Notch. Issue 2 (27th October 2020) - Lasko, Galina; Deryugin, Evgeny; Danilenko, Igor; Schmauder, Siegfried
Abstract : Small‐scaled non‐standard specimens with chevron notch (CN) from Zirconia ceramics are probed both numerically and experimentally by wedging. The original construction in the form of double cantilever beam (DCB) with CN is considered for the fracture toughness determination of ZrO2 specimens. The fracture toughness is determined in experiment on wedging of DCB with CN, with application of analytical formula derived by one of the authors and maximum force, bending the cantilever's arm. The 3D finite‐element simulations of wedge splitting test are performed using two approaches: cohesive zone modeling (CZM) approach and element elimination technique (EET). The specific fracture energy defined in experiments is taken as the input parameter for CZM simulations of crack propagation. The effect of parameters, namely, cohesive strength, and friction coefficient, between ceramic wedge and ceramic cantilever, is considered. Different traction–separation laws are implemented, and the resulting force–displacement curves are compared with experimentally obtained ones. In the CZM approach, considering the fracture energy and the predefined crack path, matching of experimental and numerical results is not achieved. In EET, in which the restrictions on the crack paths and the requirements for inputting the fracture energy are not imposed, a good match with the experimental results is achieved. Abstract : The simulations of wedge‐splitting testing of ZrO2 ceramics are performed with finite‐element method using the cohesive zone modeling (CZM) approach and an element elimination (EET) technique. The effect of different parameters, such as cohesive strength, friction coefficient, on the force–deformation curve is analyzed. The EET simulations better match with the experimental force–displacement curve.